Acceptance of Electric Car Sharing in Rural Areas - Jan Silberer; Maja Mrso; Thomas Bäumer; Patrick Müller (Journal of Advanced Transportation)
Car sharing helps promote new drive systems to early adopters, and its market share has grown continuously worldwide. However, in rural areas, car sharing still faces challenges, such as sparse populations. In urban areas, previous research has identified underlying factors in the use of car sharing. However, these findings are yet to be transferred to rural areas. Three different methodological approaches were applied in a rural municipality in southern Germany to better understand the acceptance of electric car sharing in rural areas. Firstly, a survey was conducted with 190 participants to provide an overview of underlying factors in the acceptance of electric car sharing. Secondly, interviews were conducted with 21 participants to obtain a deeper insight into these factors. Finally, a cocreation workshop was conducted with 17 participants to identify an electric car sharing model for rural areas. The results showed that performance expectancy, hedonic motivation, and facilitating conditions were the most important factors in the use of electric car sharing in rural areas, at least when presented at a conceptual level. Furthermore, an electric car sharing service with a station-based system and a service provider to distribute vehicles to stations across the municipality’s districts was voted as the most suitable model by participants. As the car sharing system was not yet implemented at the time of the survey, future studies should examine the underlying factors in the use of electric car sharing systems in rural areas at later stages of development. Moreover, the economic and technical viability of the developed electric car sharing service should be tested.